Effects of Teenage Motherhood on Psychological Wellbeing: A Case of Teenage Mothers in Kakinga Subcounty, Bunyangabu District - Mary Matsiko (Uganda Christian University, 2026)
Teenage motherhood remains a significant public health and social concern, particularly in developing countries where teenage girls often experience early pregnancy and childbearing. This study examined the effects of teenage motherhood on the psychological wellbeing of teenage mothers in Kakinga Sub-County, Bunyangabu District, Uganda. The study adopted a mixed-methods cross-sectional research design combining both quantitative and qualitative approaches. Data were collected from fifty teenage mothers through structured questionnaires, while additional insights were obtained through key informant interviews and focus group discussions involving health workers, community leaders, and social workers. Quantitative data were analyzed using descriptive statistics such as frequencies and percentages, while qualitative data were analyzed through thematic analysis. The findings revealed that a significant proportion of teenage mothers experience psychological distress manifested through stress, anxiety, sadness, and reduced self-esteem. Financial hardship, school dropout, parenting stress, and community stigma emerged as the major challenges affecting their emotional wellbeing. Despite these challenges, family support and religious engagement were identified as key coping mechanisms that help teenage mothers manage emotional stress. The study concludes that teenage motherhood significantly affects the psychological wellbeing of adolescent mothers due to limited social-support and psychosocial support services. The study therefore recommends strengthening community-based counseling services, expanding adolescent-friendly mental health programs, promoting educational reintegration for teenage mothers, and enhancing community sensitization initiatives to reduce stigma
Undergraduate research